2020
DOI: 10.1002/ejp.1674
|View full text |Cite
|
Sign up to set email alerts
|

Time course of DNA methylation in pain conditions: From experimental models to humans

Abstract: The current, revised International Association for the Study of Pain (IASP) definition of pain is as follows: "An unpleasant sensory and emotional experience associated with, or resembling that associated with, actual or potential tissue damage" (Raja et al., 2020). This current definition of pain accentuates that pain is not only a result of tissue damage but is also an individual and personal experience, influenced by many other potential factors. In recent years, it has

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 92 publications
(218 reference statements)
0
5
0
Order By: Relevance
“… 78 , 79 , 80 , 81 Of relevance to anaesthesia, epigenetics has a role to play in the perioperative period: there are data showing epigenetic links to several types of pain and also opioid addiction-misuse which may have implications for the opioid misuse crisis. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 …”
Section: Opioid Receptors Pain and Epigeneticsmentioning
confidence: 99%
“… 78 , 79 , 80 , 81 Of relevance to anaesthesia, epigenetics has a role to play in the perioperative period: there are data showing epigenetic links to several types of pain and also opioid addiction-misuse which may have implications for the opioid misuse crisis. 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 …”
Section: Opioid Receptors Pain and Epigeneticsmentioning
confidence: 99%
“…Firstly, epigenetic changes in neurogenesis, cognition, synaptic plasticity, and neurodevelopmental and neurodegenerative diseases are known to be dynamic and unstable [15,253]. Secondly, enduring epigenetic marks can exhibit intergenerational or transgenerational heritability, meaning that epigenetic modifications occurring in germline cells can become stable and persist in subsequent generations even in the absence of the original stimuli [223,254]. Tracking inherited epigenetic information and understanding its effects in subsequent generations poses a significant challenge that needs to be addressed [249].…”
Section: Epigenetics As a New Paradigm For Developing Drugs Or Strate...mentioning
confidence: 99%
“…Recent studies showed that chronic pain can be related to changes in DNA methylation, the prototypical epigenetic mechanism, leading to the modulation of pain pathways from the spinal cord to the cortex [17,18]. Moreover, methylation studies have explored epigenetic modulation in several chronic pain conditions [19][20][21], proving that these alterations can affect pain perception and evoke pathological pain responses [22].…”
Section: Introductionmentioning
confidence: 99%